Progressive encephalomyelitis with rigidity and myoclonus after thymectomy in a woman with myasthenia gravis - Qin, Lixia; Yan, Weiqian (Frontiers in Immunology, 2025)
Progressive encephalomyelitis with rigidity and myoclonus (PERM), part of the spectrum of stiff-person syndrome (SPS), is a rare neurological disorder characterized by axial and limb rigidity, painful muscle spasms, hyperekplexia, brainstem signs, and autonomic dysfunction. Here, we present the case of a 44-year-old woman with a history of myasthenia gravis (MG) who had previously undergone a thymectomy. She presented with a 20-day history of startle-induced episodes of generalized rigidity and painful spasms affecting her face, trunk, and limbs. Her symptoms began gradually, initially with numbness and pain on the right side of her face, followed by sudden episodes of myoclonus and jerking, predominantly in axial muscles, triggered by auditory stimuli and light touch. Laboratory tests revealed positive serum and cerebrospinal fluid (CSF) antibodies, including glutamic acid decarboxylase (GAD65) antibodies (titer of 1:30), α1-subunit of the glycine receptor (GlyR) antibodies (titer of 1:10), acetylcholine receptor (AChR) antibodies (>20 nmol/L), and titin antibodies (18.6 U/mL). Extensive testing ruled out other autoantibodies and tumors, leading to a diagnosis of PERM. The patient was treated with intravenous methylprednisolone, oral clonazepam, and tacrolimus, which resulted in significant clinical improvement. A 2-year follow-up demonstrated sustained recovery, accompanied by a decrease in GAD65 antibody titers. In conclusion, PERM can occur in patients with MG, even after thymectomy. Given that most patients respond well to immunosuppressive therapies, timely diagnosis and intervention are crucial.